Development of a Web-based Reservation Management System for Walters Farm - Lee Jia Mei,; Norfaradilla Wahid, (Applied Information Technology And Computer Science, 2023)
Walters Farm Reservation Management System is a web-based platform developed for online ticket purchases and streamline booking services. It aims to address issues like manual ticket entry, staff shortages, and disorganized booking management. Based on the surveys collected from the customers, Walters Farm should implement digitalization to reduce manpower, boost business volume, and increase local tourism. The prototype model is used as the methodology model for this project. For implementation, the system is developed using PHP Laravel and MySQL as the database platform. Overall, Walters Farm Reservation Management System aims to streamline the booking process that can be improved with QR code technology to provide a functional platform for both customers and staff. Based on the functional testing, it is shown that the majority of the test plan’s actual result for each module is successful. All respondents expressed satisfaction with the user interface and system functionalities.